Are Corporate Social Responsibility And Financial Ratio Matter To Earnings Quality? - Muhammad Rafi Fachruddin; Dewi Sriani (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This research aims to investigate the effect of Corporate Social Responsibility (CSR), financial ratio on earnings quality with audit committee as moderating variable. This research used quantitative method with secondary data obtained from ESGI, the Indonesian Stock Exchange (IDX) and related company websites. The population of this research is industrial and basic materials companies listed for the 2019-2022 period with 140 firm year observation as a final sample. The results show profitability has a positive effect on earnings quality. Meanwhile, CSR and liquidity has no effect on earnings quality. This study finds that the audit committee cannot strengthen the effect of CSR, profitability, and liquidity on earnings quality. Realizing that CSR that doesn’t increase earnings quality, the implication is that management may be more encouraged to establish genuine and impactful CSR programs. Shareholders can assess investment risk more properly since companies that succeed have higher earnings quality and lower risk.